2SPD-001 Introduction of an electronic ordering process for parenteral nutrition. (2nd March 2018) - Creed, M; McKiernan, M; Baker, E; Dillon, L; Ciaran, M
Abstract : Background: Parenteral nutrition (PN) is an invasive, specialised form of nutritional therapy for the prevention or treatment of malnourishment in vulnerable patients. In 2016 there was a 47% rise in PN usage, leading to workload increase and time pressures for pharmacists and dietitians working on order and supply processes. Purpose: The Pharmacy Department and Department of Clinical Nutrition and Dietetics collaboratively reviewed the PN ordering process, to remove bottlenecks and delays, and simplify communication. Material and methods: A multidisciplinary group worked through a Plan, Do, Study, Act (PDSA) cycle: The group brainstormed ideas to remove bottlenecks and streamline communication. Individual solutions were determined and trialled on an incremental basis to determine success before adding another. Prospective data was collected from September to November 2016, pre- and post-interventions trialled. Data were circulated among users on a daily basis for review. Improvements were collaboratively agreed and implemented. Results: Initial process involved dietitians sending paper prescriptions to the Pharmacy Department through a pneumatic chute system, followed by pharmacist review, order generation and bleep back to dietitians for detail verification. Updated process involves dietitians electronically ordering PN via an existing hospital ordering system, freeing up time for dietitians and pharmacists. Data analysed using Excel ® shows a 57% reduction in PN supply time in the pharmacy, from 7 to 3 min per bag (mean of 100 bags supplied per week). The dietitians and pharmacists both report improved time management and satisfaction with process update Conclusion: Introduction of a streamlined dietitian electronic ordering process for PN has led to a saving of 400 min of pharmacist time (0.18 Whole Time Equivalent) per week. The updated process has led to the capacity to accommodate the increase in service use. Furthermore, it has led to improved relations between pharmacists and dietitians, more time for communication on patient safety and stock management, and less reliance on a person-dependent manual process which previously contributed to delay and staff stress. No conflict of interest